An Observation of the Ventilatory Variables inIrritable Bowel Syndrome (IBS) Patients (The Planet, 2023)
Introduction: Irritable bowel syndrome (IBS) is a common gastrointestinal disorder characterized by abdominal pain, bloating, and bowel disturbances. While the association between IBS and other organs, such as the lungs, has been suspected for some time, it has not been thoroughly explored.The aim of the study was to observe the ventilatory variables in IBS patients ofdifferent duration and to correlate them with the duration of the disease. Methods and materials: This cross-sectional study was conducted in the Department of Physiology of Bangabandhu Sheikh Mujib Medical University, Shahbagh, Dhaka, from July 2010 to June 2011. Results: The results showed that almost all the ventilatory variables were significantly lower in the IBS patients compared to the healthy controls. Additionally, the variables were also lower in IBS patients with longer duration compared to those with shorter duration, and in group B3 compared to group B2. Furthermore, all variables were positively correlated with the duration of IBS in group B1 and FVC, FEV1 was positively correlated and FEV1/FVC% was negatively correlated with the duration of IBS in group B2. All variables were negatively correlated with the duration of IBS in group B3, but the values were not statistically significant.Conclusion: IBS patients have lower pulmonary function compared to healthy subjects, with longer duration of the disease showing greater decrease. The exact cause of this is unknown, but it is suggested that inflammation, autonomic dysfunction, and psychological disturbances may be contributing factors.
Keywords: IBS; Gastrointestinal; Spirometry; Pulmonary